Multimodality Treatments in Metastatic Gastric Cancer - Petrillo, Angelica (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Gastric cancer represents one of the most frequent and lethal tumors worldwide today, finding itself in the fifth place in incidence and the third in mortality. Surgery remains the only curative treatment for localized tumors, but only 20% of patients are suitable for surgery due to the lack of specific symptoms and the late diagnosis, especially in Western countries. Additionally, even in patients who receive curative treatment, rates of locoregional relapse and distant metastasis remain high. Palliative chemotherapy is the principal treatment in cases of metastatic disease even if the prognosis of patients receiving chemotherapy is still poor. Therefore, a multidisciplinary evaluation is important in order to improve the efficacy of active treatments. In this context, there is an unmet need for a better understanding of genetic alterations and prognostic and predictive factors in order to choose the best tailored therapy for each patient. The aim of this Special Issue is to focus on the results and problems of multimodality treatment in metastatic gastric cancer, the search for prognostic and predictive factors, and the evaluation of novel strategies for individualized treatment. We are inviting relevant original research, systematic reviews, meta-analyses, and short communications covering the above-mentioned topics.